Os militares trabalhistas na luta armada contra a ditadura civil-militar de segurança nacional no Rio Grande do Sul (1964-1971) - Trindade, Bruno Marinho (2020)
This work aims to understand the participation of the military of the Brazilian Armed Forces and the Military Brigade linked to the Brazilian Labor Party (PTB) in the armed struggle against the Civil-Military Dictatorship of National Security in Rio Grande do Sul, between 1964 and 1971. From the creation of the PTB, by Getúlio Vargas, in 1945, a part of the military that integrated the nationalist current of the Brazilian Armed Forces and the Military Brigade joined the Party or acted in defense of its programmatic line, which aimed at a series of reforms and nationalizations of economic sectors considered strategic for Brazil. In the Armed Forces, in opposition to the nationalist current, was the group of military propagators of the Doctrine of National Security (DSN), which in the context of the so-called “Cold War” (1945-1991) represented the ideological alignment with the Government of the United States of America (USA). This doctrine considered any type of individual challenge, or of social movements, to the country social inequalities, as the threat of an “internal enemy”, who would be at the service of “international communism”. Thus, this supposed enemy needed to be eliminated from society. The DSN, therefore, served as a theoretical framework for the 1964 Civil-Military Coup and for the state terrorism policy initiated that same year against civilians and military identified with nationalist and reformist, or even revolutionary ideas. In addition to framing the concept of "internal enemy", against the military identified with such ideas, there was still the aggravation of a supposed "betrayal of the country", because they were military. It is also observed that the engagement of these soldiers in the armed struggle was a continuation of the struggles that occurred in the years before the Civil-Military Coup of 1964, when they worked in the Sergeants' Movement, in the Campaign for Legality (1961), in popular mobilizations for approval of the Base Reforms and the attempt to resist the coup that deposed João Goulart, from PTB. Between 1964 and 1966 the labor military of the Armed Forces and the Military Brigade began to articulate, together with the former Governor of Rio Grande do Sul, Leonel de Moura Brizola, of the PTB, some attempts at armed movements aimed at overthrowing the newly established Dictatorship. With the abandonment of Brizola to continue the armed struggle in Brazil, in 1967, a small number of these soldiers started to act or collaborate with armed organizations of Marxist inspiration, until the moment when these were annihilated by the repressive apparatus, in Rio Grande do In 1971. Therefore, a better understanding of the performance of these military personnel was sought, during the armed struggle, taking as a theoretical reference the contributions of historical materialism and State Terrorism (TDE). In order to carry out the research, documentary sources were used – between files of repression and files on repression –, testimonies of military personnel persecuted after the 1964 Civil-Military Coup, memoir books and newspaper reports, thus making the crossing of your information.